Dying to Save: Child Sacrifice in the Harry Potter and The Hunger Games Series - Williams, Jeffrey (Journal of religion and popular culture, 2018)
J. K. Rowling's Harry Potter series and Suzanne Collins's The Hunger Games series feature the sacrifice of children in ways that reflect the lasting cultural fascination with sacrifice and participate in a wider contemporary conversation that both contests and inscribes the sacrifice of children for a variety of purposes. Whereas a deity's founding or protection of a city or nation has long been central to myths of child sacrifice, thereby linking sacrifice to religious and political ends, the Harry Potter and The Hunger Games series elevate friends and loved ones over civic structures as the primary motivations for the child's willing sacrifice. While these sacrifices ultimately take place within a larger social crisis and have social implications in both series, social change emerges only as a fragile byproduct of a willing self-giving dominated by personal concern for friends and family. Even more, while willing sacrifices for others appear paramount in both series, the novels also raise important reasons for caution in the celebration of sacrifice.